Evaluasi Pelaksanaan Program Pembelajaran Karakter di Sekolah - Zahara Bancin, Nurul; Putri Salam, Renilda Putri Salam; Tri Puspita, Maulida; Winata, Chandra; Baihaqi, Fajar (Faidatuna, 2023)
Evaluation is part of the learning process which as a whole cannot be separated from teaching activities, carrying out evaluations carried out in educational activities has a very important meaning, because evaluation is a measuring instrument or process to find out the level of success achieved by students at zas teaching materials or the materials that have been delivered, so that with an evaluation, the objectives of learning will be seen accurately and convincingly. Program evaluation is a series of activities carried out deliberately and carefully to determine the level of implementation or the success of a program by knowing the effectiveness of each each component, both for the ongoing program and past programs. Character education can be referred to as moral education. Moral education, if successfully achieved, can form a good personality in accordance with Islamic religious teachings regarding the basic morals, ethics, character, good habits that produce changes in the spiritual and physical development of students